Attention-Deficit/Hyperactivity Disorder (ADHD) in Adulthood: Concordance and Differences between Self- and Informant Perspectives on Symptoms and Functional Impairment - Mörstedt, Beatrice; Corbisiero, Salvatore; Bitto, Hannes; Stieglitz, Rolf-Dieter (PLOS ONE, 2015)
Attention-deficit/hyperactivity disorder (ADHD) is a severe mental illness, associated with major impairment and a high comorbidity rate. Particularly undiagnosed ADHD in adulthood has serious consequences. Thus, a valid diagnosis is important. In adulthood, the diagnostic process for ADHD is complicated: symptoms may overlap with comorbid disorders, and the onset and progression of the disorder must be reconstructed retrospectively. Guidelines for the diagnostic process recommend the inclusion of additional informant ratings. Research into the relation between self- and informant ratings shows extremely heterogeneous results. The levels of agreement range from low to high. The focus of this study is the concordance and differences between self- and informant ratings on ADHD symptoms and impairments. In this regard, two possible influencing factors (gender and relationship type) are also examined. 114 people participated in this study, 77 with an ADHD diagnosis and 37 without a diagnosis. For all participants, either parents or partners also rated ADHD symptoms and impairments. Small to moderate concordance was found between self- and informant ratings, with females being slightly more concordant than males, particularly for ratings of problems with self-concept. Examination of the consistency within a particular perspective showed that people with ADHD seemed to be unaware of the causal relation between ADHD symptoms and their impairments. A close investigation found almost no influence of gender and relationship type on differences within perspectives. Based on these results, the implications for the diagnostic process are that additional informant information is clearly necessary and helpful.